The quality of general dental care: public and users' perceptions. Issue 3 (1st September 1999) - Calnan, M; Dickinson, M; Manley, G
Abstract : BACKGROUND: Systematic evidence about how the public and users perceive and experience the quality of general dental care is in short supply, particularly in light of the recent changes in the general dental service. The study reported here attempted to fill this gap. OBJECTIVES: To identify the criteria the public and users adopt in evaluating the quality of general dental care, and to identify the extent and nature of perceived concerns with general dental care. DESIGN: Postal questionnaires were sent to random samples of adults living in an inner city area (I) and semi-rural area (R) in southern England. Fifty six per cent (1499) in area R and 48% (1388) in area I completed the questionnaire after four mailings. Follow up face-to-face interviews were done with a purposive subsample (n = 50) of responders from the postal survey. MAIN MEASURES: Public/user views about quality of dental care were measured through groups of questions about the importance of and satisfaction with different aspects of dental care (access/availability including cost; facilities; technical skills; and interpersonal care) and a scale (Dentsat) measuring general satisfaction was constructed from questions on different aspects of care. RESULTS: Evaluation of quality of general dental care from the users' point of view hinges on perceived technical skills, particularly pain management. Major dissatisfaction stems from concerns about costs of dental care and privatisation. CONCLUSIONS: The criteria adopted by the public/users to assess general dental care are similar to other areas of health care, apart from the priority placed on technical skills and pain management. However, the major source of decline in satisfaction with the quality of general dental care is the barrier to access created by the rising cost of dental care and the increasing involvement of dentists in private practice. This evidence suggests that the public and users find the drift towards private practice and away from NHS practice a major source of concern.